SYUJETLI LIRIKANÍŃ QÁLIPLESIWI HÁM RAWAJLANÍW BASQÍShLARÍ - Dosımbetova, Abadan Alievna; Jalgasbaeva, Ayzada Abdulla qızı (SCIENCE and SOCIETY, 2026)
This article discusses the formation and developmental stages of narrative lyric, a form of lyric poetry in fiction. Additionally, it analyzes the initial plot elements found in lyric poetry.